PERAN MODEL PEMBELAJARAN KOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA JARING-JARING PELANGI TERHADAP HASIL PEMBELAJARAN MATEMATIKA DI SDN 6 SUWAWAL - Cahyaningrum, Suciati; Safitri, Kristantina; Sutriyani, Wulan (LPPM Universitas Bina Bangsa, 2024)
This study aims to explore the role of the Make a Match type Cooperative Learning Model supported by the Rainbow net media in improving mathematics learning outcomes at SDN 6 Suwawal. The research method used was a pseudo-experiment with a pre-test post-test control group design. The research subjects consisted of two randomly selected classes, one class as an experimental group that applied the Make a Match type cooperative learning model assisted by Rainbow net media, and one class as a control group that received conventional learning. Data were collected through tests of mathematics learning outcomes before and after treatment. The results showed that the Make a Match type cooperative learning model assisted by Rainbow net media significantly improved mathematics learning outcomes compared to conventional learning. These findings suggest that the use of cooperative learning models supported by interactive media can be an effective alternative in improving students' mathematical understanding and achievement at the elementary level. This research makes an important contribution to the development of learning methods that are more oriented towards student involvement and the use of technology in the learning process